Life of St. Pancratius: Clarification of Terms and Reconstruction of Book Writing and Icon Painting Realia in the 10th and 11th Centuries - Kseniia S. Morugina (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2020)
Introduction. The paper attempts to compare and analyze specific words identifying book writing and icon painting realia in the Life of St. Pancratius thereby providing new definitions for these terms. In the light of the results obtained, it became possible to propose a reconstruction of book writing and icon painting at the time described in the Life of St. Pancratius.